(untitled) (Journal of National Institute of Neurosciences Bangladesh, 2025)
Background: Chronic inflammatory demyelinating polyradiculoneuropathy (CIDP) is a rare and heterogeneous immune-mediated neuropathy. Objectives: The aim of this study was to evaluate the clinical and electrophysiological aspects of CIDP in adult. Methodology: This cross-sectional study was carried out in the department of Neurophysiology of National Institute of Neurosciences and Hospital, Bangladesh from July 2020 to July 2022. We included 50 consecutive patients aged 18 years to 70 years fulfilling criteria for CIDP proposed by the European Federation of Neurological Societies and the peripheral nerve society, 2010. These patients were evaluated by detailed history, physical examination and electrophysiological findings. Results: The mean age was 43.82 ± 13.43year. Males were more affected than female. Weakness and paresthesia were the most common symptoms. 92% patients had a progressive and 8% had relapsing course. Most patients were classified as typical CIDP (90.0%) and 92.0% patients had electrophysiological definite CIDP. Conclusion: CIDP affects males mostly in the 3rd to 5th decades. Typical CIDP was most common. Weakness in both proximal and distal muscle groups along with paresthesia were the most common symptoms. Few patients had distal wasting. Diabetes mellitus was associated disease in 36% of the cases. Journal of National Institute of Neurosciences Bangladesh, January 2025;11(1):34-40